Identification of wound-response proteins associated with gaharu formation in Aquilaria malaccensis Lam via proteomic analysis - Hishamuddin, Muhammad Syahmi (2018)
Aquilaria malaccensis is a native tree in Malaysia that produce aromatic oleoresin known as gaharu in response to biotic and abiotic stress. Gaharu is a highl-value non-timber product due to its important role in fragrance, aromatherapy, medicines and religious activities. Little is known about gaharu formation in the wood. Mechanical wounding is a major trigger for the formation of gaharu in the tropical tree taxa Aquilaria. To understand the molecular mechanism by which Aquilaria reacts to wounding, we applied the proteomic approach using liquid chromatography coupled with mass spectroscopy (LC/MS-MS). Proteins were extracted from wounded area on the stems of 5-year old trees as a result of a drilling method. Changes in the A. malaccensis stem tissue proteomes were examined at 0, 2, 6, 12, and 24 hours after wounding treatment and led to the identification of 2227 differentially expressed proteins. The identified proteins were then undergone Venn diagram analysis resulting with 564 time-point specific proteins with 25% overlap among the five time points. All of the 564 time-point specific proteins were then grouped into biological process categories by using Gene ontology and REViGO analysis and based on these analyses, 21 wound-response proteins were successfully identified. Identification of a set of wound-response proteins that is part of the plant defense system and proteins that are involved in gaharu formation in A. malaccensis tree provides a valuable reference for further studies.